EVALUATION OF PHYSICAL CAPABILITIES IN SOCCER PLAYERS OF U-15- & U-17 CATEGORIES (Fiep Bulletin - online, 2014)
The Soccer is showing a concern for athletes from the basic categories, with intervening evaluative techniques used to identify variables relevant to the performance of athletes throughout their training. Factors such as aerobic capacity, anaerobic and anthropometric aspects are important to be evaluated in order to verify the fitness of these athletes. Thus, the intent of this study was to evaluate the physical valences in soccer players U-15 and U-17, from tests commonly applied to this sport. We evaluated 13 male adolescents, athletes practicing a particular football club, aged 16 ± (0.95) years. The results were different in some studies capabilities when compared with similar groups. For evaluation of BMI, body fat percentage and muscle power with the long jump, the results were good compared to the literature, but in the aspect of aerobic capacity and VO2 max and average power, the results show low values. According to the values obtained conclude that these athletes are at a lower level is necessary for successful actions in football for the category. It is essential and important, the development of a new strategic training plan for athletes aiming to work efficiently these factors.
Keywords: Assessment; Physical capacities; Soccer